A METHOD FOR MULTI-BLOCK PARALLEL DECOMPOSITION OF A SYSTEM OF PARTIAL BOOLEAN FUNCTIONS - Yu. V. Pottosin (Informatika)
A method for multi-block parallel decomposition of a system of partial Boolean functions represented by a pair of ternary matrices is described. The method involves examining the row orthogonality graphs of those matrices. It is reduced to finding the complete bipartite subgraphs (bicliques) in one of those graphs and finding a shortest cover of the row set of the other graph by those bicliques.